Transforming Learning Outcome Assessment through the Implementation of the Digital Madrasah Report Card at MI Al-Markaz Al-Islami Maros - Maryam Djasdar; Muljono Damopolii; Muhammad Yaumi (al-Afkar, Journal For Islamic Studies, 2026)
Transformation of the learning outcome assessment system is an important part of educational innovation efforts, especially in the digital era. This study aims to analyze the implementation of the Raport Digital Madrasah (RDM) at MI Al-Markaz Al-Islami Maros as a step in modernizing the learning outcome assessment system. The methodology used is descriptive qualitative with data collection techniques through observation, interviews, and document analysis. This study involved teachers, students, and administrative staff as the main subjects. The results of the study indicate that the implementation of digital report cards can improve the efficiency of the assessment process, data accuracy, and openness of information to parents of students. This system also makes it easier for teachers to manage student academic data systematically. The use of the Raport Digital Mardrasah (RDM) has made a significant contribution to improving the quality of learning outcome assessment at MI Al-Markaz Al-Islami Maros. Technological support and teacher competency development are needed to ensure the sustainability of this innovation.